The problem of improvement and effective application of modular learning with a knowledge control rating system (Pedagogy of Higher and Secondary Education, 2009)
The article is devoted to the problem of effective application of the module teaching with the rating checking system of knowledges.
Keywords: module; module estimation; module teaching rich in content module; rating; module-rating checking system